Cryptococcosis--a review of 13 autopsy cases from a 54-year period in a large hospital - Kašparová, Petra; Buchta, Vladimír; Cerman, Jaroslav; Žák, Pavel (APMIS. Acta pathologica, microbiologica et immunologica Scandinavica, 2007)
From 1952 to 2005, 13 cases of cryptococcosis confirmed by postmortem examination were diagnosed in autopsy material from the University Hospital in Hradec Králové, the Czech Republic. Histologically, Cryptococcus was found in multiple organs (brain and spinal cord, lungs, lymph nodes, spleen, bone marrow, liver, kidneys and adrenal glands). The lungs and CNS were the organs most often involved. Only in two cases was the diagnosis of cryptococcal infection established during the patient's lifetime, in both presenting clinically as meningitis, with positive result of CSF cultivation. Data and issues of diagnostics and treatment of cryptococcosis are discussed.
Keywords: financování organizované; dospělí; Female; Cause of Death; Adult; ženské pohlaví; lidé; Cryptococcosis; Cryptococcus neoformans; Financing, Organized; retrospektivní studie; Male; kryptokokóza; Aged; Czech Republic; fagocytóza; Phagocytosis; Česká republika; lidé středního věku; senioři; mužské pohlaví; příčina smrti; Retrospective Studies; Middle Aged; Humans